Stopping Powers of Alpha Particles in Some Gases At Energies From 1.0 to 6 MeV - Khiem, Le Hong; Trong, Tran Dinh; Nghia, Nguyen The (Communications in Physics, 2016)
Stopping powers of \(α\)-particles emitted by \(^148\)Gd, \(^241\)Am and \(^243\)Cm isotopes in PR10 and isobutane(C\(_4\)H\(_10\)+Ar) gases have been experimentally measured in the energy region from 1.0 to 5.5 MeV. The experimental data were compared with those calculated by SRIM-2013 computer code. It was concluded that the experimental stopping powers in our investigated region are in agreement with the calculated values.